Analysis of spontaneous reports of suspected adverse reactions after vaccination against COVID-19 in Slovakia - Lassanova, Monika; Lassan, Stefan; Liskova, Silvia; Tesar, Tomas; Cicova, Monika (Frontiers in Pharmacology, 2023)
Introduction: The COVID-19 pandemic has resulted in more than 6.5 million deaths worldwide yet. Vaccination against the SARS-CoV-2 virus is a reliable way out of the pandemic, however, vaccination rate reaches only 39% in the Slovak Republic. Concerns about the adverse reactions of vaccines are one of the reasons for the low vaccination rate. Objective: The aim of our analysis was to review reported suspicions of adverse reactions (ARs) of registered COVID-19 vaccines (Comirnaty, Vaxzevria, Spikevax), which State Institute for Drug Control received from healthcare professionals and patients in the period from 1st January 2021 to 31st May 2021. Methods: Data were collected from the State Institute for Drug Control database, a retrospective analysis was carried out focusing on trends in the number of all reports of suspicions of ARs sent to the State Institute for Drug Control during the previously mentioned period. We analysed the Retrieved data were analysed with the usage of descriptive statistics and comparison to historical data on drug ARs in Slovakia was performed. Results: During the evaluation period, 5763 reported suspicions of ARs were analysed, overall, there was a significant (p <0.0001) increase in the number of reported ARs fivefold. 93% of ARs (n = 5346) were reported for COVID-19 vaccines. In comparison of the extentof all ARs, there is clearly a statistically significant difference between all types of vaccines administered at that time (p≤0.0001). No statistically significant difference (p≤0.238) was identified between Spikevax and Comirnaty in the proportion of serious ARs. However, a significantly higher (p≤0.00001) proportion of reported suspicions of serious ARs was observed after the administration of Vaxzevria. Conclusion: This is the first analysis conducted in Slovakia aimed to reported ARs in relation to the administration of COVID-19 vaccines. The rate of spontaneously reported suspected ARs has been insufficient in the past for a long time; during the period from January to May 2021 the reporting rate increased due active calls for ARs reporting. In concordance with European data, Vaxzevria had a significantly higher ratio of reported suspicions of serious ARs.